2004
DOI: 10.1103/physrevb.69.161101
|View full text |Cite
|
Sign up to set email alerts
|

Charge fluctuations and electron-phonon interaction in the finite-UHubbard model

Abstract: In this paper we employ a gaussian expansion within the finite-U slave-bosons formalism to investigate the momentum structure of the electron-phonon vertex function in the Hubbard model as function of U and n. The suppression of large momentum scattering and the onset a small-q peak structure, parametrized by a cut-off qc, are shown to be essentially ruled by the band narrowing factor ZMF due to the electronic correlation. A phase diagram of ZMF and qc in the whole U -n space is presented. Our results are in m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 17 publications
7
28
0
Order By: Relevance
“…For high temperatures the boundaries of the phase-separated state were determined in the T-U plane for different dopings and the increase of the static vertex ⌫ near the boundaries was studied, confirming and extending recent results of Ref. 17. At low temperatures and moderate or small dopings we found that ⌫ does not exhibit pronounced forward scattering behavior and that ⌫ reduces dramatically the electron-phonon coupling.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For high temperatures the boundaries of the phase-separated state were determined in the T-U plane for different dopings and the increase of the static vertex ⌫ near the boundaries was studied, confirming and extending recent results of Ref. 17. At low temperatures and moderate or small dopings we found that ⌫ does not exhibit pronounced forward scattering behavior and that ⌫ reduces dramatically the electron-phonon coupling.…”
Section: Discussionsupporting
confidence: 88%
“…This has also been pointed out in Ref. 17. Calculating the phase diagram, we find a very peculiar reentrant behavior around the phase separated region for finite U as shown in Fig.…”
Section: Phase Separationsupporting
confidence: 88%
“…The latter effect is more pronounced at lower doping. The similar (to Monte Carlo) results were obtained quite recently in [15] in the framework of the Rückenstein-Kotliar (four slave-boson) model. These numerical results prove the correctness of the FSP theory of the EPI, which are based on the X-method.…”
Section: Pairing and Transport Epi Coupling Constantssupporting
confidence: 69%
“…This fundamental result allows us to resolve a number of experimental puzzles, which can not be explained by the old Migdal-Eliashberg theory based on the momentum independent (isotropic) EPI. The most important predictions of the FSP theory which includes the EPI and other charge We stress the following two facts coming from the theoretical analysis: (i) the forward scattering peak in the EPI of strongly correlated systems is a general phenomenon by affecting electronic coupling to all phonons; (ii) the existence of the forward scattering peak in the EPI is confirmed numerically by the Monte Carlo calculations for the Hubbard-Holstein model with finite U [14], by exact diagonalization [65], as well as by some approximative theoretical methods [15].…”
Section: Discussionmentioning
confidence: 91%
“…We stress the following two facts coming from the theoretical analysis: (i) the forward scattering peak in the EPI of strongly correlated systems is a general phenomenon by affecting electronic coupling to all phonons; (ii) the existence of the forward scattering peak in the EPI is confirmed numerically by the Monte Carlo calculations for the Hubbard-Holstein model with finite U [21], by exact diagonalization [124], as well as by some other methods [22].…”
Section: Discussionmentioning
confidence: 99%